Antenatal depression and associated factors among HIV-positive pregnant women in South Gondar zone public health facilities, northwest Ethiopia, a cross-sectional study - Selam Yibeltal Desalegn; Mengstu Melkamu Asaye; Wubedle Zelalem Temesgan; Marta Berta Badi (Elsevier, 2022)
Introduction: Depression and HIV/AIDS are estimated to be the world's two leading causes of burden of disease by 2030. Depression during pregnancy is a significant public health problem because it has negative effects on the health of the mother and her fetus. However, evidence on antenatal depression and associated factors among HIV-positive women is scarce in the study area. Objective: This study was aimed to assess antenatal depression and associated factors among HIV-positive pregnant women attending prevention of mother to child transmission service in South Gondar zone public health facilities, northwest Ethiopia. Methods: Institutional-based cross-sectional study was conducted on 606 HIV-positive pregnant women. The data were collected by face-to-face interviews and chart review. Edinburgh Perinatal Depression Scale was used to assess antenatal depression. Data were entered into Epi-Data version 4.6 and analyzed by SPSS version 23. Multivariable logistic regression model was fitted and AOR with 95% CI was computed to determine the level of significance. Results: The prevalence of antenatal depression was 36.4% (95% CI: 32.7, 40.2). Being unmarried (AOR = 2.77, 95% CI: 1.26, 6.07), experienced intimate partner violence during this pregnancy (AOR = 1.50, 95% CI: 1.05, 2.15), ART non -adherence (AOR = 2.18, 95% CI: 1.50, 3.18), and experienced internalized AIDS stigma (AOR = 1.46, 95% CI: 1.02, 2.09) were significantly associated with antenatal depression. Conclusion and recommendation: In this study, more than one-thirds of HIV-positive pregnant women had antenatal depression. Screening HIV-positive pregnant women for depression and provision of intervention is recommended.